2016
DOI: 10.1080/09513590.2016.1232215
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal outcome in pregnancies complicated with gestational diabetes mellitus and very preterm birth: case–control study

Abstract: Preterm birth is defined as all births before 37 completed weeks of gestation. Preterm birth can be further sub-divided based on gestational age: extremely preterm (528 weeks), very preterm (28 to 532 weeks) and moderate preterm (32 to 537 weeks). Retrospective observational casecontrol study review (1 year i.e., 2015) is to assess pregnancy outcome among women with gestational diabetes mellitus (GDM) delivering very preterm (28 + 0/7 to 31 + 6/7 weeks of gestation). The study group included all women diagnose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 21 publications
0
10
1
Order By: Relevance
“…Neonatal admission to NICU was 65%; this finding was less than study done Russia [23] showed that 100% neonatal NICU admission but study done in Saudi Arabia [17] which was less than this finding. This difference may be due to neonatal health care strategy they apply.…”
Section: Discussionmentioning
confidence: 54%
“…Neonatal admission to NICU was 65%; this finding was less than study done Russia [23] showed that 100% neonatal NICU admission but study done in Saudi Arabia [17] which was less than this finding. This difference may be due to neonatal health care strategy they apply.…”
Section: Discussionmentioning
confidence: 54%
“…Preterm birth is defined as delivery before the gestational week 37 or day 259 [13]. It has been the most concerning complication among pregnant women and affects 10% of all pregnancies.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is not new, although recent literature on this issue suggests that well-controlled maternal gestational diabetes does not impose an increased risk for infants' BPD. [48][49][50] A limitation of this study is the fact that maintaining peripheral saturations 90 to 95% early and over 95% once 36 weeks may affect generalizability of our results. A significant proportion of the US and other countries centers target 87 to 93% (or thereabouts) prior to 33 to 34 weeks then over 90% afterward, and BPD rates are different among centers that use different criteria.…”
Section: Discussionmentioning
confidence: 93%